An An accurate molecular method to sex elephants using PCR amplification of Amelogenin gene - George Lohay (Pachyderm)
The use of molecular methods to identify the sex of elephants from non-invasive samples is essential for studies of population dynamics and population genetics. We designed a new technique for sex identification in elephants using Amelogenin (AMEL) genes. The X-Y homologs of AMEL genes are suitable for sex determination in pigs and some bovids. In this study on savannah elephants, the use of AMEL genes was more successful than previous methods that relied on genes found exclusively on Y-chromosomes, such as SRY, to distinguish males from females. We designed a common forward primer and two reverse primers for X- and Y-specific AMEL genes to obtain 262bp and 196bp PCR amplicons from Y and X genes, respectively. We tested the primers for the identification of the sex of 132 savannah elephants from fecal samples.  The sex of 126 individuals (95.45%) matched observational data, while 6 (4.54%) did not match. This discrepancy observed was due to observational errors in the field, where high grass  reduces the ability to accurately sex young individuals. Through our stool samples results, we have shown that the use of only three primers for AMELX/Y provides a highly accurate PCR-based method for sex identification in savannah elephants. The method is fast and shows more success than the SRY system by avoiding the inherent ambiguities of the previous PCR-based methods that made it difficult to distinguish between female samples and failed amplification reactions. Our sex identification method is non-invasive and can potentially be applied in population genetic studies and forensics tests on both savannah as well as forest elephants.